# Question #c15cb

##### 1 Answer

Mar 26, 2016

#### Answer:

Any pair where

#### Explanation:

The average rate of change of the function

#(f(b)-f(a))/(b-a)#

Since we know this is equal to

#(f(6)-f(3))/(6-3)=2#

#(f(6)-f(3))/3=2#

#f(6)-f(3)=6#

Thus, any pair of values where

#{(f(3)=0),(f(6)=6):}#

You could also have any of the following pairs. (Remember, the only thing that must hold true is that

#{(f(3)=-2),(f(6)=4):}#

#{(f(3)=1/2),(f(6)=13/2):}#

#{(f(3)=-200),(f(6)=-194):}#

#{(f(3)=pi),(f(6)=pi+6):}#